A novel evaluation technique for radiochromic films based on cosine-distance analysis: Feasibilities of wide range photon dosimetry and postal intercomparison in lieu of conventional TLD chips. (January 2022) - Mukherjee, Bhaskar; Bhonsle, Uday
Abstract: Photon radiation induced decolourisation of radiochromic film changes its optical density. The photon dose is thereby evaluated as a function of optical density. The detection limit of common radiochromic films lies between 1 cGy and 20 Gy. This paper describes a novel evaluation method of radiochromic films using cosine-distance analysis of the RGB-colour vectors instead of conventional optical density measurements using a scanner in transmission mode. This allows extending the detection limit to excess of 40 Gy. Highlights: Gaf-EBT3 radiochromic films exposed to photons from 6 MV linac. RGB colour histogram constructed using ImageJ program. Cosine-distance (CD) calculated using RGB colour vectors. Photon doses presented as a function of CD.